2017
DOI: 10.1039/c7nr04686c
|View full text |Cite
|
Sign up to set email alerts
|

High thermal conductivity through simultaneously aligned polyethylene lamellae and graphene nanoplatelets

Abstract: The effect of simultaneous alignment of polyethylene (PE) lamellae and graphene nanoplatelets (GnP) on the thermal conductivity (k) of PE-GnP composites is investigated. Measurements reveal a large increase of 1100% in k of the aligned PE-GnP composite using 10 wt% GnPs relative to unoriented pure PE. The rate of increase of k with applied strain for the pure PE-GnP composite with 10 wt% GnP is found to be almost a factor of two higher than the pure PE sample, pointing to the beneficial effect of GnP alignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…The λ value of the Py-PGMA-GNPs/epoxy composite with 4 phr Py-PGMA-GNPs was increased to 1.91 W/mK, about 20 times graphite content (80-200 phr) to obtain the comparable λ value. Garg et al [149] fabricated the GNP/PE composites with ultrahigh λ value via the simultaneous alignment of PE lamellae and GNPs. The λ value of the aligned GNPs/PE composite with 10 wt% aligned GNPs was significantly enhanced to 5.90 W/mK, increased by 1100% compared to that of unoriented original PE matrix.…”
Section: Carbon-based Fillersmentioning
confidence: 99%
“…The λ value of the Py-PGMA-GNPs/epoxy composite with 4 phr Py-PGMA-GNPs was increased to 1.91 W/mK, about 20 times graphite content (80-200 phr) to obtain the comparable λ value. Garg et al [149] fabricated the GNP/PE composites with ultrahigh λ value via the simultaneous alignment of PE lamellae and GNPs. The λ value of the aligned GNPs/PE composite with 10 wt% aligned GNPs was significantly enhanced to 5.90 W/mK, increased by 1100% compared to that of unoriented original PE matrix.…”
Section: Carbon-based Fillersmentioning
confidence: 99%
“…Additionally, dispersed fillers can cause an unstable TC during solid–liquid phase transitions . To make full use of the geometric and dimensional properties of sheet‐like fillers, they are generally assembled and oriented into an aligned structure by pressure‐induced compression, vacuum‐assisted self‐assembly/alignment, solution casting, mechanical strain, electric‐field‐assisted orientation, or ice‐templated assembly to obtain a structurally anisotropic framework. The individual fillers act as building blocks of the framework, which serves as the thermally conductive matrix in a composite.…”
mentioning
confidence: 99%
“…The individual fillers act as building blocks of the framework, which serves as the thermally conductive matrix in a composite. Thermally conductive polymer‐based composites using an aligned GNP framework have been developed for thermal interface materials (TIMs) . The reported Κ comp at near room temperature can reach approximately 17 W m −1 K −1 .…”
mentioning
confidence: 99%
“…Table 3 2007 [120] 2007 [120] 2014 [122] 2016 [121] 2016 [123] carbon [131]. Saeidijavash et al [25] reported an increase of 60% in κ c of the aligned PE-GNP composite using 10 wt.% GNP relative to oriented pure PE using mechanical strain. Table 5 summarizes the enhancement of κ in PE and PP using graphenebased materials.…”
Section: Simulation Of Thermal Conductivity In Polymer Compositesmentioning
confidence: 99%
“…Therefore, using filler with high κ f combined with the simultaneous alignment of PE chains and the embedded filler, κ c can be significantly enhanced. For instance, κ c of PE composite containing 10 wt.% graphene nanoplatelets has reached 5.9 W/m·K after stretching the composite, indicating the great potential to fabricate polyolefin composites with high κ c [ 25 ].
Figure 2.
…”
Section: Introductionmentioning
confidence: 99%